“Self as enterprise”: overmarketization and the self-management of R&D engineers - Xia Yan (SpringerOpen, 2021)
Abstract This article analyzes the self-enterprising mechanism of research & development (R&D) engineers based on a case study of labor control in a high-tech company. The concept of “self as enterprise” refers to the form of labor control by allowing workers to self-manage according to the market principle. It is neither a form of normative control built upon accepting and internalizing market-oriented values nor responsible autonomy aiming to enhance workers' organizational commitment. R&D engineers' reproduction of current living standards depends heavily on performance-based salaries, which forces them to pragmatically comply with market rules. When both the reproduction of labor and the labor market have been overmarketized, R&D engineers are at high risk of downgrading their living standards and facing double job insecurity. Therefore, they must manage their work and life in an enterprising way to maximize labor value and prevent it from being devalued.